2007
DOI: 10.1590/s1519-566x2007000600021
|View full text |Cite
|
Sign up to set email alerts
|

Eclosion rate, development and survivorship of Aedes albopictus (Skuse)(Diptera: Culicidae) under different water temperatures

Abstract: Neotropical Entomology 36 (6):966-971 (2007) Eclosão, Desenvolvimento e Sobrevivência de Aedes albopictus (Skuse) (Diptera: Culicidae) sob Diferentes Condições de Temperatura da Água RESUMO -Em áreas tropicais, onde as populações de insetos vetores são particularmente abundantes, as temperatura usualmente variam entre 25°C e 35°C. Considerando a importância dessa variação na determinação da dinâmica populacional de mosquitos, neste trabalho, desenvolvimento e as taxas de eclosão e sobrevivência dos estágios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
3
31
0
2
Order By: Relevance
“…As expected, the total development time (from irst instar larva to adult emergence) was inversely related to the rearing temperature in the range of 7 o C to 25 o C, as observed for several mosquito species (e.g., Rueda et al 1990, Mahamood & Crans 1998, Ribeiro et al 2004, Monteiro et al 2007. The time required by the immatures maintained at the lowest temperatures to reach adulthood was extended between six to eight orders of magnitude as compared for those maintained at 25°C.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…As expected, the total development time (from irst instar larva to adult emergence) was inversely related to the rearing temperature in the range of 7 o C to 25 o C, as observed for several mosquito species (e.g., Rueda et al 1990, Mahamood & Crans 1998, Ribeiro et al 2004, Monteiro et al 2007. The time required by the immatures maintained at the lowest temperatures to reach adulthood was extended between six to eight orders of magnitude as compared for those maintained at 25°C.…”
Section: Resultssupporting
confidence: 76%
“…Pupal survivorship ranged from 5% (5/92) at 7°C up to 13% (12/92) at 15°C, and no larvae completed their development in temperatures > 30 o C (Table 1). Nevertheless, other culicids common to the south of Brazil and Argentina are able to complete their development in temperatures between 30 o C and 35ºC (Calado & Navarro-Silva 2002, Ribeiro et al 2004, Monteiro et al 2007. However, none of them have been detected on latitudes higher than 40ºS.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our experiment food was supplied in optimum amounts, and evidence exists that under such nutritional conditions, larval developmental period vary from 5 to 10 days [36] . Monteiro et al [37] recorded no adult emergence when immature stages of A. albopictus were maintained at 35 曟 and concluded that the limit temperature for the development of its larval stages is close to 35 曟 . Our result is consistent with a similar previous study in Penang [17] in indicating a short larval period of A. albopictus, although the environmental conditions are not identical.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred Ae. aegypti eggs approximately 15 days old were used to avoid lowering the hatching rate [16] [17]. To check the incubation period and viability, the eggs were divided into five batches of 20 eggs each, which were kept in 20 mL test tubes, with 10 mL of water and fish food added to each tube.…”
Section: Biological Assays On Ae Aegypti Eggsmentioning
confidence: 99%